Single best answer questions for dentistry - Biyani, Prateek (Hoboken, NJ : Wiley-Blackwell, 2021)
'With over 280 questions, Single Best Answer Questions for Dentistry is an invaluable resource for those preparing for upcoming dental examinations including Membership of the Joint Dental Faculties (MJDF), Member of the Faculty of Dental Surgery (MFDS) and the Overseas Registration Exam (ORE). Covering a range of specialties in dentistry such as restorative dentistry, oral surgery, oral pathology, paediatrics, and periodontology, the book provides a quick and easy way to revise. Each question has an associated answer and explanation leading to a more thorough and complete revision tool'--
Restorative dentistry -- Oral medicine -- Oral surgery -- Oral pathology -- Paediatric dentistry and orthodontics -- Periodontics -- Pharmacology and human disease -- Dental materials -- Radiology.
Includes index.
Keywords: Dentistry; Examination Questions